2024
DOI: 10.1021/acssensors.3c02207
|View full text |Cite
|
Sign up to set email alerts
|

Cluster-Enhanced Nanopore Sensing of Ovarian Cancer Marker Peptides in Urine

Thomas W. Rockett,
Mohammed Almahyawi,
Madhav L. Ghimire
et al.

Abstract: The development of novel methodologies that can detect biomarkers from cancer or other diseases is both a challenge and a need for clinical applications. This partly motivates efforts related to nanopore-based peptide sensing. Recent work has focused on the use of gold nanoparticles for selective detection of cysteine-containing peptides. Specifically, tiopronin-capped gold nanoparticles, trapped in the cis-side of a wild-type α-hemolysin nanopore, provide a suitable anchor for the attachment of cysteine-conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Recent research utilizing biological nanopores has demonstrated their capability to detect protein biomarkers uniquely present in the urine of ovarian cancer patients. 34 Furthermore, these nanopores are extensively used in analysing protein conformations and protein–ligand interactions. 35–37…”
Section: Introductionmentioning
confidence: 99%
“…Recent research utilizing biological nanopores has demonstrated their capability to detect protein biomarkers uniquely present in the urine of ovarian cancer patients. 34 Furthermore, these nanopores are extensively used in analysing protein conformations and protein–ligand interactions. 35–37…”
Section: Introductionmentioning
confidence: 99%